Glucose-6-phosphate dehydrogenase is indispensable in embryonic development by modulation of epithelial-mesenchymal transition via the NOX/Smad3/miR-200b axis - Wu, Yi-Hsuan (Cell Death Dis, 2018)
Glucose-6-phosphate dehydrogenase (G6PD) is a housekeeping enzyme involved in the pentose phosphate shunt for producing nicotinamide adenine dinucleotide phosphate (NADPH). Severe G6PD deficiency leads to embryonic lethality, but the underlying mechanism is unclear. In the current study, the effects of G6PD on epithelial–mesenchymal transition (EMT), especially during embryonic development, were investigated. The knockdown of G6PD induced morphological changes, accompanied by the suppression of epithelial markers, E-cadherin and β-catenin, in A549 and MDCK cells. Such modulation of EMT was corroborated by the enhancement of migration ability in G6PD-knockdown A549 cells. Zebrafish embryos with g6pd knockdown exhibited downregulation of the E-cadherin/β-catenin adhesion molecules and impaired embryonic development through reduction in epiboly rate and increase in cell shedding at the embryo surface. The dysregulation in zebrafish embryonic development caused by g6pd knockdown could be rescued through human G6PD or CDH1 (E-cadherin gene) cRNA coinjection. The Smad3/miR-200b axis was dysregulated upon G6PD knockdown, and the reconstitution of SMAD3 in G6PD-knockdown A549 cells restored the expression of E-cadherin/β-catenin. The inhibition of NADPH oxidase (NOX) activation through the loss of p22(phox) signaling was involved in the dysregulation of the Smad3/miR-200b axis upon G6PD knockdown. The reconstitution of G6PD led to the recovery of the regulation of NOX/Smad3/miR-200b signaling and increased the expression of E-cadherin/β-catenin in G6PD-knockdown cells. Thus, these results suggest that in the EMT process, G6PD plays an important regulatory role as an integral component of the NOX/Smad3/miR-200b axis.